Acta Historiae Neerlandicae - Prevenier, W. author. aut Link
VII, 265 p.
Keywords: The editors of the seventh volume of Acta Historiae Neerlandicae have followed the same lines as those adopted for its predecessor. Studies have again been selected which throw light on the history of the Low Countries, the choice again being directed to subjects likely to be of interest to foreign scholars lacking knowledge of the Dutch language. For this reason articles fairly general in scope have been chosen: studies of local interest or concerned with matters of detail have not been included. In this volume a wide diversity of topics is treated. Included are studies in the economic and social history of the later Middle Ages, and on subjects in the fields of the sixteenth and early half of the eighteenth centuries. There are two articles on the nineteenth century Dutch statesman Thorbecke (1972 was the anniversary of his death). And there are also contributions on the homeland of Erasmus and on Dutch reactions to the publication of Darwin's Origins of Species. Also included are surveys of recent historical publications in the Netherlands and of those from Belgian historians that appeared in Dutch. A group of English historians, working under the guidance of Professor Swart, of University College, London, has surveyed the former, this article being edited by Mrs Alice Carter of the London School of Economics. The task of the late Professor Dhondt, of the University of Ghent, in connection with the survey of the Belgian contributions written in Dutch has been taken over by W.